2005
DOI: 10.1118/1.2126821
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric comparison of versus for HDR prostate brachytherapy

Abstract: For the purpose of evaluating the use of 169Yb for prostate High Dose Rate brachytherapy (HDR), a hypothetical 169Yb source is assumed with the exact same design of the new microSelectron source replacing the 192Ir active core by pure 169Yb metal. Monte Carlo simulation is employed for the full dosimetric characterization of both sources and results are compared following the AAPM TG-43 dosimetric formalism. Monte Carlo calculated dosimetry results are incorporated in a commercially available treatment plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
1
28
1
Order By: Relevance
“…These results are in agreement with previous publications by other investigators such as the report by Andrássy et al indicating that 60 Co and 192 Ir delivered similar dose distributions in the treated volume. Lymperopoulou et al had shown that the plan quality with 169 Yb at least is equivalent to 192 Ir source irrespective of the prostate volume. It was also shown that, by modifying the applicator, the HDR 60 Co afterloading system can be a good alternative to the HDR 192 Ir, delivering similar dose distributions in breast cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous publications by other investigators such as the report by Andrássy et al indicating that 60 Co and 192 Ir delivered similar dose distributions in the treated volume. Lymperopoulou et al had shown that the plan quality with 169 Yb at least is equivalent to 192 Ir source irrespective of the prostate volume. It was also shown that, by modifying the applicator, the HDR 60 Co afterloading system can be a good alternative to the HDR 192 Ir, delivering similar dose distributions in breast cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…20 Maughan's combustion analysis measurements show that mineral ash content of excised tumors ranges from 0.9% to 3%, leading to dose estimation errors as large as 15% at 28 keV. 113 For higher energy sources, there is evidence that air-tissue boundaries forming the breast and lung contours can perturb HDR breast implant doses by 5% to 10% at lower doses ͑Ͻ60% of D 90 ͒ for 192 Ir while for lower energy 169 Yb, D 90 is lower than predicted by conventional dose planning by 5% and as much as 25% at lower doses. 87 No studies systematically assessing the impact of compositional ͑in contrast to density͒ heterogeneities on higher energy sources are available.…”
Section: Iie Accounting For Heterogeneities In Dose Calculationsmentioning
confidence: 99%
“…166 HDR 192 Ir for prostate brachytherapy has been a treatment choice for two decades, with a role primarily for large glands. 167,168 A recent possible alternative is HDR 169 Yb, which has lower photon energies than 192 Ir and a potentially more advantageous dose distribution for localized treatment. 98,169 Similarly, LDR 131 Cs sources, commercially available since 2004, emit photon energies slightly higher than those of 125 I.…”
Section: Iiib Prostate Implantsmentioning
confidence: 99%
“…Bare point sources were used to speed up simulations given that dose distribution anisotropy is not of interest to this work, combined with the fact that source and encapsulation design do not significantly affect the dose distribution along the transverse source bisector of 192 Ir 15 and 169 Yb sources. 16 The initially emitted photon spectrum for 169 Yb and 192 Ir were taken from the NuDat database, 17 and nonpenetrating photons of energy lower than 10 keV were not taken into account. The photon simulation cutoff energy was set to 5 keV and the cross section libraries were customized for equivalence with the DLC-146 compilation.…”
Section: Iia Monte Carlo Simulationsmentioning
confidence: 99%